A Proposed National Archaeological Database for Oman " NADO" - Al Belushi, Mohammad Ali K. (أدوماتو, 2012)
Keywords: Archéologie -- Oman

Contribution to the Flora of Central-Southern Dhofar (Sultanate of Oman) - Mosti, Stefano; Raffaelli, Mauro; Tardelli, Marcello (Webbia, 2012)
From 2000 to 2009 we carried out 10 scientific missions to Central-Southern Dhofar with the aim of collecting plants. We eplored several habitats, such as littorals and seashores, coastal plains and many wadis ending in the Arabian sea (from Rackhyt, Al Mughsayl, Salalah, Khor Rori, Mirbat, Hadbin up to Hasik). We paid particular attention to the floristic exploration of the monsoon slopes of the coastal mountains (with special reference to Jabal Qara) where plant richness and endemic taxa are mostly concentrated. Plants were also collected on the upper part of Jabal Samhan, the highest mountain of Dhofar, in the pre-desertic area of Wadi Andur, beyond Jabal Samhan and in several areas where, nowadays, large groups of Boswellia sacra, the frankincense tree, grow, i.e. Al Mughsayl, Adownib, Aluf, Uyun, Wadi Dowkah and Hasik. Sporadic explorations were carried out on the vaste pre-desertic area that, from Thumrayt, spreads northward to the Saudi Arabia border, from Muddy, Al Mathafah, Ginan Bin Nawatish to Shisr (the ancient Ubar), Sayh al Kharyat and Dawkah. The number of explored sites (233) was large enough to have exhaustive information on the local distribution of the species. The collected taxa are 606; 17 of them are first records from Oman, 13 are first record from Dhofar. As regards endemics, 14 taxa are endemic to Dhofar, while 35 are regional endemics, distributed in Oman/Dhofar & Yemen; most of these are concentrated on the monsoon slopes of the coastal mountains.
Keywords: Botanique -- Oman

سمات الدرس العقدى عند الشيخ بيوض - الشيهاني, حمو بن عيسى (دراسات إسلامية, 2012)
Keywords: Bayyūḍ, Ibrāhīm ibn ʿUmar (1899-1981)

التاريخ والمؤرخون في وارجلان الاباضية على عهد الموحدين: أبو يعقوب يوسف بن إبراهيم الوارجلاني نموذجا - زيدور, عبد الحميد (مجلة عصور الجديدة, 2012)
Keywords: Biographies -- Ouargla; Ouargla -- Histoire

التواجد المذهبي في السودان الغربي بين القرنين الخامس والعاشر للهجرة - شعباني, نور الدين (دورية كان التاريخية, 2012)

آفاق دراسة المخطوط بين الضيق والسعة: المخطوط الإباضي أنموذجا في المكتبات الخاصة في معاقل الإباضية بالجزائر وتونس وليبيا - الباروني, سناء مهني (التراث, 2012)
إن مجادلة السائد في التعامل مع المخطوط بالمغرب الإباضي موقف نقدي يخترق المألوف، وأفق منهجي ومعرفي يتخطى المتداول بحثا عن الجديد وتوقا للبديل في تحيين المعرفة بإرث مادي وفكري ضاربة جذوره في القدم من أجل ثقافة حية متطورة. ونوجه عنايتنا في هذا العمل إلى الفحص والاستقراء ثم النقد للمخزون الإباضي في شكله المخطوط من خلال انموذجه بالجزائر وتونس وليبيا سعيا لطرح أليات نظر جديدة كإضافات ملائمة ومطلوبة للتعامل مع هذا النوع من المؤلفات بما هي فضاء لا يزال بكرا في العديد من جوانبه. وإذا كان المخطوط الإباضي المغاربي بوادي ميزاب الجزائري وجزيرة جربة التونسية وجبل نفوسة الذي هو وعاء لمضمون فکري وحضاري مشترك له مميزاته وخصوصياته، فإنه في شكله موضوع معرفة أخرى لها قوانينها ومميزاها و خصوصياتها أيضا. ذلك أن سيرورة حياة هذا المخطوط ليست سوى انعكاس لسيرورة فكر ظهرت أسس مدرسته منذ النصف الثاني من القرن الأول للهجرة في خضم أحداث الفتنة الكبرى وما عقبها من وقائع كانت وراء ظهور الفرق الإسلامية .والإباضية واحدة من بين تلك الفرق التي أدلت بدلوها عقائديا وسياسيا وفكريا على وجه الخصوص منذ ذلك الزمن، وقد صان أتباعها الذين انحدروا من صلب المحكمة • أصول فكرهم ومبادئهم ونشر أئمتهم تعاليم الدين عبر حملة العلم الذين جابوا الأمصار مشرقا ومغربا لنشر أصول مذهبهم عقيدة وفقها.
Keywords: Bibliothèques -- Ibadisme

نشأة الحواضر الإباضية الميزابية وتطورها من خلال مخطوط مالكي لصاحبه السيد أحمد بن التومي مع تقييد للشيخ بن القاسم العطفي - يطو, فتيحة (المجلة المغاربية للمخطوطات, 2012)
نشأة الحواضر الإباضية الميزابية وتطورها من خلال مخطوط مالكي لصاحبه السيد أحمد بن التومي مع تقييد للشيخ بن القاسم العطفي

المرأة الإباضية وإسهامها في الحركة الثقافية لبلاد المغرب - بلهواري, فاطمة (مجلة الحضارة الإسلامية, 2012)
المرأة الإباضية وإسهامها في الحركة الثقافية لبلاد المغرب

الحياة الاقتصادية في زنجبار في عهد سعيد بن سلطان 1832-1856 - جريذي, أحمد راشد; العيساوي, مصلح محمد عبد (مجلة جامعة الأنبار للعلوم الأنسانية, 2012)

النفوذ البريطاني وتجارة الرقيق في الخليج العربي في القرن التاسع عشر - شطب, جاسم محمد (مجلة جامعة كربلاء, 2012)

Tahkîm Telakki̇si̇ne Eleşti̇rel Bi̇r Yaklaşim (i̇bâziye Örneği) - Ateş, Orhan (Dicle Üniversitesi İlahiyat Fakültesi Dergisi, 2012)
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-

المستظهرون لكتاب الله العزيز بالقرارة (1432 1433 / 2011 2012) (الحياة, 2012)

الصلح والوساطة في القانون الجزائري - أبو بكر, صالح بن عبد الله (الحياة, 2012)

في رثاء الشيخ الناصر بن محمد المرموري (قصيدة) - إتبيرن, رستم بن عيسى (الحياة, 2012)
Keywords: Poésie -- Mzab

قراءة تحليلية نقدية في شرح إسماعيل الجيطالي للمنظومة النونيَّة... - الباروني, سناء مهني (الحياة, 2012)

منهج فقهاء الإباضية في التعامل مع السنَّة - الحاج امحمد, قاسم بن عمر (الحياة, 2012)
Keywords: Fiqh

المفهوم الغائب - الشيخ أحمد, عيسى بن عمر (الحياة, 2012)

الافتتاحية - الشيخ بالحاج, عيسى بن محمد (الحياة, 2012)

العلامة الشيخ ناصر بن محمد المرموري في عليين - الشيخ بالحاج, عيسى بن محمد (الحياة, 2012)

سمات الدرس العقدي عند الشيخ إبراهيم بيوض - الشيهاني, حمو بن عيسى (الحياة, 2012)
Keywords: Bayyūḍ, Ibrāhīm ibn ʿUmar (1899-1981)

كتاب بدء الإسلام وشرائع الدين للواب بن سلام الإباضي - الطرابلسي, حنان الحسين (الحياة, 2012)

التفسير الشفاهي وأثره في الإصلاح الحديث - الوزناجي, نادية (الحياة, 2012)

البشرية الحائرة ودور العالِم، على ضوء السراج النبوي - بابا عمِي, محمد بن موسى (الحياة, 2012)

حكم نكاح مزنية الرجل ومزنية غيره (دراسة مقارنة بين الفقه الإباضي والمالكي) - باحامد, إدريس بن بابه (الحياة, 2012)
Keywords: Fiqh

مصادر تاريخ إباضية المغرب في العصور الوسطى - بحاز, إبراهيم بن بكير (الحياة, 2012)

المشروع الثقافي للاستعمار الفرنسي في الجزائر ومقاومته في مِزاب - بن عمر, موسى بن بكير (الحياة, 2012)
Keywords: Mouvement national -- Mzab

قواعد في البناء الحضاري - بوحجام, محمد بن قاسم ناصر (الحياة, 2012)

الإمام الربيع بن حبيب ومُسندُه - بولرواح, إبراهيم بن علي (الحياة, 2012)

الزاوية وبعد القبيلة في منطقة «توات» (رؤية سوسيولوجية) - بوهناف, عبد الكريم; باشيخ, أسماء (الحياة, 2012)

رسالة الشيخ بيوض إلى آل بريان «رسالة شكر وعرفان» - جهلان, محمد بن أحمد (الحياة, 2012)
Keywords: Bayyūḍ, Ibrāhīm ibn ʿUmar (1899-1981)

مقدار ديَّة الخطأ بالعملات المتداولة - حمدي, محمد بن صالح (الحياة, 2012)

الاستعارة القرآنية؛ أثرها النفسي وجمالها البلاغي - دوادي, زينب (الحياة, 2012)

الفتوى بين التشدد والتيسير والاعتدال - شتوان, بلقاسم (الحياة, 2012)
Keywords: Fatwas -- Ibadisme

قراءة في نماذج من مراسلات القطب إلى أهل عمان (الحلقة الثالثة) - شريفي, مصطفى بن محمد (الحياة, 2012)
Keywords: Relations -- Mzab -- Oman

شوقي وحافظ في ميزان الرافعي - لقدي, محمد (الحياة, 2012)

جهود حماية مخطوطات وادي مزاب وقراءة وصفية لفهارسها - باباواسماعيل, زهير بن مسعود (مجلة التراث, 2012)
Keywords: Manuscrits -- Conservation; Manuscrits -- Mzab

النسيج العمراني لمدن وادي مزاب - معروف, بالحاج بن بنوح; جودي, محمد (مجلة منبر التراث الأثري, 2012)
Keywords: Archéologie -- Mzab

‏منهج الشيخ إبراهيم بيوض العقدي في تفسيره في رحاب القرآن عرض ودراسة - الشعيلي, سليمان بن علي (مجلة قطاع أصول الدين, 2012)
Keywords: Bayyūḍ, Ibrāhīm ibn ʿUmar (1899-1981)

In the Time of Oil: Piety, Memory & Social Life in an Omani Town. Mandana E. Limbert. Stanford, CA: Stanford University Press, 2010 - Gilbert, Paul (Anthropology of Work Review, 2012)
Keywords: Recension

Review of The Mehri Language of Oman - Morris, Miranda (Journal of the American Oriental Society, 2012)
Keywords: Recension

Founder mutations in Tunisia: implications for diagnosis in North Africa and Middle East - Romdhane, Lilia; Kefi, Rym; Azaiez, Hela; Halim, Nizar Ben; Dellagi, Koussay; Abdelhak, Sonia (Orphanet Journal of Rare Diseases, 2012)
Background: Tunisia is a North African country of 10 million inhabitants. The native background population is Berber. However, throughout its history, Tunisia has been the site of invasions and migratory waves of allogenic populations and ethnic groups such as Phoenicians, Romans, Vandals, Arabs, Ottomans and French. Like neighbouring and Middle Eastern countries, the Tunisian population shows a relatively high rate of consanguinity and endogamy that favor expression of recessive genetic disorders at relatively high rates. Many factors could contribute to the recurrence of monogenic morbid trait expression. Among them, founder mutations that arise in one ancestral individual and diffuse through generations in isolated communities. Method: We report here on founder mutations in the Tunisian population by a systematic review of all available data from PubMed, other sources of the scientific literature as well as unpublished data from our research laboratory. Results: We identified two different classes of founder mutations. The first includes founder mutations so far reported only among Tunisians that are responsible for 30 genetic diseases. The second group represents founder haplotypes described in 51 inherited conditions that occur among Tunisians and are also shared with other North African and Middle Eastern countries. Several heavily disabilitating diseases are caused by recessive founder mutations. They include, among others, neuromuscular diseases such as congenital muscular dystrophy and spastic paraglegia and also severe genodermatoses such as dystrophic epidermolysis bullosa and xeroderma pigmentosa. Conclusion: This report provides informations on founder mutations for 73 genetic diseases either specific to Tunisians or shared by other populations. Taking into account the relatively high number and frequency of genetic diseases in the region and the limited resources, screening for these founder mutations should provide a rapid and cost effective tool for molecular diagnosis. Indeed, our report should help designing appropriate measures for carrier screening, better evaluation of diseases burden and setting up of preventive measures at the regional level.
Keywords: Génétique -- Djerba

Autoritarisme et stratégies de légitimation dans le golfe Persique à l'heure du « Printemps arabe » - Valeri, Marc (Revue internationale de politique comparée, 2012)
Keywords: Vie politique -- Oman -- 1970-2020

موقف بريطانيا من الوجود السياسي والعسكري الأمريكي في عُمان 1932-1945 - محمود, ادريس حردان (مجلة الدراسات التاريخية والحضارية, 2012)

الدور السياسي للقبيلة: سلطنة عمان أنموذجاً - الزيود, اسماعيل; الطراونة, فاطمة (دراسات, 2012)
The aim of the study is to highlight the main role which the Omani tribe played in transforming the Sultanate of Oman from a State governed by tribes to a state with a political system and to elaborate on the power struggle between the El-Yaa'ribeh tribe and the Bursa'idiyyin tribe which led to the rise of a unified state amid the competition of foreign powers, such as France and Britain to gain control of the Sultanate. The study concluded that the Bursa'idiyyin tribe played an important political role in the history of Oman by contributing to the formation of the contemporary Omani State. The Bursa'idiyying tribe is still playing its role in the contemporary state of Oman. The study has confirmed that the Omani tribe was and still is the basis of the political system of Oman and that it is the main supporter of the regime. It has also confirmed the success of the role of the tribe in accessing power while keeping the tribe 's components as a social unit in the Omani Society.
Keywords: Tribalisme -- Oman

التفريق القضائي بين الزوجين من اجل العيوب الموجودة في الرجل دراسة مقارنة بين الاباضية والحنفية - بكلي, ابراهيم بن عبد الله (مجلة الواحات للبحوث والدراسات, 2012)
Keywords: Fiqh

Un explorateur oublié, Paul Blanchet (1870-1900) - Descamps, Cyr; Rosière, Pierre (Images et Mémoires, 2012)
Keywords: Biographies -- France

North African Jewish and non-Jewish populations form distinctive, orthogonal clusters - Campbell, C. L.; Palamara, P. F.; Dubrovsky, M.; Botigue, L. R.; Fellous, M.; Atzmon, G.; Oddoux, C.; Pearlman, A.; Hao, L.; Henn, B. M.; Burns, E.; Bustamante, C. D.; et al. (Proceedings of the National Academy of Sciences, 2012)
North African Jews constitute the second largest Jewish Diaspora group. However, their relatedness to each other; to European, Middle Eastern, and other Jewish Diaspora groups; and to their former North African non-Jewish neighbors has not been well defined. Here, genome-wide analysis of five North African Jewish groups (Moroccan, Algerian, Tunisian, Djerban, and Libyan) and comparison with other Jewish and non-Jewish groups demonstrated distinctive North African Jewish population clusters with proximity to other Jewish populations and variable degrees of Middle Eastern, European, and North African admixture. Two major subgroups were identified by principal component, neighbor joining tree, and identity-by-descent analysis—Moroccan/Algerian and Djerban/Libyan—that varied in their degree of European admixture. These populations showed a high degree of endogamy and were part of a larger Ashkenazi and Sephardic Jewish group. By principal component analysis, these North African groups were orthogonal to contemporary populations from North and South Morocco, Western Sahara, Tunisia, Libya, and Egypt. Thus, this study is compatible with the history of North African Jews—founding during Classical Antiquity with proselytism of local populations, followed by genetic isolation with the rise of Christianity and then Islam, and admixture following the emigration of Sephardic Jews during the Inquisition.
Keywords: Génétique -- Afrique du Nord

Enslaved Population and Indian Owners Along the East African Coast: Exploring the Rigby Manumission List, 1860–1861 - Suzuki, Hideaki (History in Africa, 2012)
The main purpose of this article is to explore the potential of the "List of Slaves unlawfully held in slavery by British Indian Subjects at Zanzibar & its Dependencies, who have been emancipated at the Consulate" for historical slavery studies. This list, a result of the first British-led manumission campaign against slave ownership along the east coast of Africa, is the most comprehensive list detailing slave ownership and slaves for the pre-colonial coastal society of East Africa. Despite of the importance and uniqueness, both this list and the campaign have not been yet fully analyzed. This article challenges to extract the data as much as possible from the list, not only sex ratio and ethnic origin of enslaved individuals, but also their identity and emotional status. Moreover, this article shows an aspect of slave ownership by British Indian subjects from the list.
Keywords: Esclavage -- Zanzibar

الحركة الوطنية التونسية في سنوات مابين الحربين 1918–1939 - التكريتي, غيلان سمير طه (جملة آداب الفراهيدي, 2012)
Keywords: Mouvement national -- Tunisie

Journal de Libye - Kepel, Gilles (Le Débat, 2012)

“A Sea of Blood and Plunder”. Lutte contre la traite et politique impériale britannique dans l'océan Indien vers 1820-1880 - Crouzet, Guillemette (Monde(s), 2012)
Sur la base du vaste corpus des archives britanniques, cet article étudie la construction d’un « espace-réseau » de la traite des esclaves aux intégrations économiques variées, centré sur le Golfe, la mer d’Oman et le Nord de l’Océan Indien, et fondé sur la ramification complexe des routes d’approvisionnement des esclaves. Les zones fournissant les travailleurs captifs, la diversité des marchés acheteurs, de l’Empire ottoman et ses harems aux sociétés de la Péninsule arabique, sont mises en valeur, ainsi que la « profondeur » spatiale de ce système économique régional. Cette étude adopte, par ailleurs, un point de vue original sur l’action des Britanniques : les Anglais, en signant des traités avec les puissances régionales de l’espace – la Perse, l’Empire ottoman, les Pachas indépendants d’Égypte, le Sultan omanais ou encore les shaikhs de la « Côte de la Trêve » – ont peu à peu bâti un territoire politique transnational « normé » par ces mêmes accords, et « policé » par les patrouilles de l’Indian Navy et de la Royal Navy.
Keywords: Esclavage -- Oman

Początki i pierwszy tom „Rocznika Orientalistycznego”. Przyczynek do dziejów czasopisma - Dobosz, Krzysztof (LingVaria, 2012)
Keywords: Smogorzewski, Zygmunt (1884-1931)

The ethnic label Zinjibari: Politics and language choice implications among Swahili speakers in Oman - Kharusi, Nafla S. (Ethnicities, 2012)
The ethnic label Zinjibari in Omani society has various connotations that depend on who is using the term and about whom it is being used. Through participant observation and within the context of ethnolinguistic identity theory, this qualitative study aims to demonstrate how the label Zinjibari can function as an outgroup or ingroup label, as a mark of solidarity, as a term of prestige or as a slur. It is also proposed that these different connotations influence language choice among Oman’s Swahili speakers.
Keywords: Emigration -- Zanzibar -- Oman

Per un uso corretto del Linguaggio Scientifico : Perché non esiste une civiltà rupestre - Caprara, Roberto (Umanesimo Della Pietra, 2012)

الشيخ سالم بن يعقوب: حياة رجل وتجربة جيل ج١ - البوجديدي, علي (الحياة, 2012)

Seyyid Said bin Sultan BuSaid of Oman and Zanzibar: Women in the Life of this Arab Patriarch - Romero, Patricia W. (British Journal of Middle Eastern Studies, 2012)
Seyyid Said bin Sultan BuSaid, ruler of Oman (1806 – 1856) and of Oman and Zanzibar (1836– 1856) owed his Omani throne to his fraternal aunt. He married her daughter, his cousin, and cast a wide net for nocturnal partners—slaves from mainly the Black Sea and Abyssinia. He married two Persian royals, and courted the Queen of Madagascar. This paper covers the major events in Said’s life from the death of his father, Sultan, in 1904 when his aunt stepped in to aid him (and a brother with whom he became co-ruler for a few years), until Said’s death at sea in 1856. Suffering losses of territory his predecessors had gained in the Persian Gulf, Said created a domestic empire in Zanzibar.
Keywords: Vie politique -- Oman -- 1804-1856

تأثيرات اندلسية في شعر أبي مسلم الرواحي جوانب أدبية و فنية مقارنة - هيكل, سمير (2012)
Keywords: Poésie -- Oman

L’apport des sources ibadites à la toponymie médiévale du Nafzāwa (Sud Tunisien) - Prevost, Virginie (Al-Andalus Magreb, 2012)
Keywords: Ibadisme -- Nefzaoua

الحياة الثقافية في منطقة مزاب خلال العصرين الوسيط والحديث - بوراس, يحيى بن عيسى (مجلة الواحات للبحوث والدراسات, 2012)

طارق بن تيمور ومحاولته عزل السلطان سعيد بن تيمور 1962-1970 - العمري, ثابت غازي بدر; هياجنه, رائد أحمد (مجلة جامعة الخليل للبحوث, 2012)
This paper essentially examines Tariq Bin Timur’s character and his achievements during the reign of his brother Sultan Sa’id Bin Taimur (1932 – 1971). The paper also highlights the motives behind his departure of the Sultanate in 1966 and announcing his discretion to oust the Sultan on the grounds that he was behind the backwardness of the Sultanate.To this end, Tariq made a statement in which he called on the Omani people for support, with a view of ousting the Sultan. In the process, he wrote the Sultanate’s future constitu- tion hoping that his efforts would prevail. With respect to the position of the British Government and other influential parties, the paper looks critically into their positions, particularly that of the British Government, which firmly opposed any change threat that would threat its interests
Keywords: Vie politique -- Oman -- 1932-1970

صنع القارر السياسي في سلطنة عمان - السعدون, واثق محمد (دراسات إقليمية, 2012)

Discovery of the earliest royal palace in Gao and its implications for the history of West Africa - Takezawa, Shoichiro; Cisse, Mamadou (Cahiers d'études africaines, 2012)
Keywords: Archéologie -- Mali

Berbères de Libye : un paramètre méconnu, une irruption politique inattendue - Chaker, Salem; Ferkal, Masin (Politique africaine, 2012)
Keywords: Vie politique -- Djebel Nefousa

Oman : The “Forgotten” Corner of the Arab Spring - Worrall, James (Middle East Policy, 2012)
Keywords: Vie politique -- Oman -- 1970-2020

The Battle of Mirbat: turning point in the Omani Dhofar rebellion - Martinez, Ian Illych (Small Wars & Insurgencies, 2012)
Keywords: Dhofar

Epidemiological investigation of keratinophilic fungi from soils of Djerba (Tunisia) - Anane, S. (Journal de Mycologie Médicale, 2012)
Keywords: Botanique -- Djerba

Religious tolerance in Oman: addressing religious prejudice through educational intervention - Sadi, Fatma H. al-; Basit, Tehmina N. (British Educational Research Journal, 2012)
Keywords: Tolérance religieuse -- Oman

The efficacy of Ottoman counter-intelligence in the 16th century - Gürkan, Emrah Safa (Acta Orientalia Academiae Scientiarum Hungaricae, 2012)
This article examines the Ottoman counter-intelligence mechanism and the extent to which it succeeded in preventing enemy intelligence. In the 16th century, the length and the scope of both Ottoman – Habsburg and the Ottoman Safavid Rivalry convinced the Ottomans to establish an intelligence network that gathered information in a large geography. Nevertheless, in the war of information between the Ottomans and their rivals, the success of Ottoman information-gathering was intertwined with the efficiency of Ottoman counter-intelligence. In order to gain an advantage in “politics of information”, the Ottoman secret diplomacy successfully refused its enemies a comfort which it sought for itself: access to information about the adversary.
Keywords: Ottomans -- Djerba

Wedding ceremonies and cultural exchange in an Indian Ocean port city: the case of Zanzibar Town - Issa, Amina A. (Social Dynamics, 2012)
Keywords: Zanzibar

Saharan trade in the Roman period: short-, medium- and long-distance trade networks - Wilson, Andrew (Azania: Archaeological Research in Africa, 2012)
Keywords: Commerce transsaharien

Images de la femme maghrébine: analyse comparative de Je dois tout à ton oubli et La saison des hommes - Tonda, Ángeles Llorca (Anales de Filología Francesa, 2012)
In the artistic productions object of my study, Malika Mokeddem novel, Je dois tout à ton oubli (2008) and the Tunisian film director Rachida Tlatli, La saison des hommes (2000), evokes the theme of resignation and submission of women to the power of men in the North African context. The parallel analysis of the novel and film will allow me to highlight the convergent narrative structures used in both works to denounce women’s alienation and despair that some of them manifest. Similarly enunciate what are the loopholes that both the novelist and the director proposed to the heroines of their stories.

Cheveux et poils dans le judaïsme - Michel, K. (Anthropology of the Middle East, 2012)
Keywords: Judaïsme -- Djerba

Zanzibari Islamic knowledge transmission revisited: loss, lament, legacy, transmission – and transformation - Bang, Anne K. (Social Dynamics, 2012)
Keywords: Zanzibar

سليمان باشا الباروني والجزائر - سعد الله, أبو القاسم (مجلة الدراسات التاريخية, 2012)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Italian archaeologists in colonial Tripolitania - Munzi, Massimiliano (Libyan Studies, 2012)
This is a contribution to a reassessment of colonial archaeology in Libya, based on the academic and political/ ideological portraits of the archaeologists serving in the Tripolitanian and (from 1936) Libyan Soprintendenza. Italian colonial archaeologists were, often deliberately, instruments of political strategy. They searched for traces of Rome in the nationalistic context of the Libyan War, and sought to reconstruct an idealised vision of the Roman cities during the Fascist Ventennio. The essential continuity between nationalist archaeology of the Liberal period (1910–1922), characterised by the central idea of the civilising force of Rome as a tool of colonial expansion, and the Fascist archaeology of 1922–1943, in which the integration of archaeology with political aims touched on the extreme, sometimes with grotesque results, will be stressed and a chronological overview presented. Negative judgment should be nuanced by placing the colonial archaeology in its historical context, analysing its structure, remembering that its methodological backwardness was shared by metropolitan archaeology, noting the high quality of the restoration work and finally by comparing Italian fieldwork with that of other European excavations in North African or Near Eastern protectorates and colonies. It is not a case of presenting a revisionist interpretation, but of approaching the subject without prejudice.
Keywords: Archéologie -- Djebel Nefousa

Shaping of the Sharia courts: British policies on transforming the kadhi courts in colonial Zanzibar - Hashim, Abdulkadir (Social Dynamics, 2012)
Keywords: Zanzibar

Review of John C. Wilkinson. Ibadism: origins and early development in Oman - Gaiser, Adam R. (Jerusalem Studies in Arabic and Islam, 2012)
Keywords: Recension

Des églises byzantines converties à l’islam ? Quelques mosquées ibadites du djebel Nafûsa (Libye) - Prevost, Virginie (Revue de l’histoire des religions, 2012)
La population berbère du djebel Nafûsa était majoritairement chrétienne lorsqu’elle a adopté massivement la doctrine ibadite à la fin de la première moitié du viiie siècle. Cette région conserve de nombreuses mosquées qui portent des noms associés au christianisme, qui font référence aux apôtres ou sont directement issus du latin ecclesia. Les sources ibadites laissent penser qu’il s’agit d’églises byzantines reconverties en mosquées. Cependant, si l’origine chrétienne du bâtiment apparaît distinctement dans un des exemples étudiés, la plupart de ces mosquées n’ont sans doute aucun lien avec d’anciennes églises. Leur nom évoque simplement le souvenir du passé chrétien de la région.
Keywords: Christianisme -- Djebel Nefousa

Review of Early Ibāḍī Literature. Abu l-Mundhir Bashīr b. Muḥammad b. Maḥbūb. Kitāb al-Raṣf fi l-Tawḥīd, Kitāb al-Muḥāraba and Sīra. (Abhandlungen für die Kunde des Morgenlandes, 75) - Prevost, Virginie (Wiener Zeitschrift für die Kunde des Morgenlandes, 2012)
Keywords: Recension

L’aventure ibadite dans le Sud tunisien: Effervescence d’une région méconnue - Aillet, Cyrille (Al-Masāq, 2012)
Keywords: Recension

Abdel-Hakim Ourghi, Die Reformbewegung in der neuzeitlichen Ibāḍīya. Leben und Wirken von Muḥammad b. Yūsuf Aṭfaiyaš 1236–1332 h.q. (1821–1914), Würzburg: Ergon-Verlag 2008. 399 S., ISBN 978-3-89913-660-9. Preis: € 52.– - Schmidinger, Thomas (Der Islam, 2012)
Keywords: Recension

جهود العلماء المغاربة في خدمة اللغة العربية : من خلال التراث المخطوط حاشية سليمان الجربي على مختصر التفتازاني نموذجا - حاج أمحمد, يحيى بن بهون (مجلة الباحث, 2012)

مؤسسة الآباء البيض الفضاء الديني والاقتراب المجتمعي : ملامسة سوسيو تاريخية بمنطقة غرداية - خواجة, عبد العزيز بن محمد; عمر, داود (مجلة الناصرية للدراسات الاجتماعية والتاريخية, 2012)
Keywords: Christianisme -- Mzab

فرسطاء موقعها الجغرافى وآثارها التاريخية والثقافية فى جبل نفوسة - حامد, سعيد علي (مجلة البحوث التاريخية, 2012)

الخوارج والمعارضة في التاريخ الإسلامي - قويدر, بشار (مجلة الحكمة, 2012)
Keywords: Kharijisme

حوار ابن عباس الدعوي مع الخوارج : أصوله وآدابه وأساليبه " دراسة تحليلية - الزهراني, محمد بن إبراهيم (مجلة العلوم الشرعية, 2012)
تأتي هذه الدراسة لتسلط الضوء على حادثة دعوية قديمة جديدة، تتكرر منذ بزوغ فجر الإسلام على مر الأجيال بذات الشبه الفكرية، ونظرا لما تضمنه حوار تلك الحادثة من ثراء معرفي يؤسس لعملية الاتصال الدعوي مع الخوارج فقد رأى الباحث أهمية دراسة حوار ابن عباس رضي الله عنهما مع الخوارج. فتحدث فيه عن مفهوم حوار ابن عباس الدعوي مع الخوارج، والمضامين الدعوية التي أتت في ثنايا ذلك الحوار، وهي أصول الحوار الدعوي وآدابه وأساليبه ونتيجة ذلك الحوار الدعوى. ثم خرج الباحث بعدد من الدروس الدعوية المستفادة من حوار ابن عباس الدعوي من الخوارج، والتي تسهم في إعداد داعية يحاور أرباب الفكر المنحرف، كما خرج بعدد من النتائج والتوصيات الدعوية.
Keywords: Kharijisme

حركة الخوارج في القرن الهجري الأول / السابع الميلادي : دراسة لمواقفهم ومعتقداتهم من قضايا الإستعراض والتكفير والجهاد والولاء والبراء - ملحم, عدنان مبارك (مجلة البحوث والدراسات الإنسانية الفلسطينية, 2012)
ارتبط ظهور حركة الخوارج عام (37 هـ/ 657 م)، بتطورات الصراع في معركة صفين، بين المعسكر الشامي بقيادة معاوية بن أبي سفيان (ت 60 هـ/ 679 م)، والمعسكر العراقي بقيادة علي بن أبي طالب (ت 40 هـ/ 660 ه (. وتمثل حركة الخوارج جبهة المعارضة الرئيسة ضد النظام السياسي الحاكم ، وتعد من أكثر الحركات توظيفا للدين من أجل تحقيق أهدافها المختلفة. تبنت حركة الخوارج شعارات ووسائل مختلفة، هدفت في معظمها إلى إلغاء الآخر ورفضه، وعدم الحوار معه. ويتناول الباحث موقفها من أربع قضايا هامة شكلت في مجموعها استراتيجيتهم الثابتة في ذلك، وهي :- الاستعراض ، والتكفير ، والجهاد، والولاء والبراء ويستعرض الباحث تأثير حركة الخوارج على منهج الحركات الأصولية (الإسلامية) المعاصرة وأفكارها، متخذا من جماعة التكفير والهجرة أنموذجا لذلك.
Keywords: Kharijisme

معركة النهروان 38 هـ - سليمان, أسامة بن علي (التوحيد, 2012)
Keywords: Fitnah

الإباضية و المرجئة : دراسة مقارنة - عرض و نقد - المدهون, مي بنت حسن محمد (مجلة مركز البحوث والدراسات الإسلامية, 2012)

موقف إمارة عمان من السلطة البويهية - سعيد, عمر أحمد (آداب الرافدين, 2012)
ظهرت إمارات في الجزيرة العربية ولاسيما في عمان فأخذه على عاتقها التصدى للسلطة البويهية لأنها أرادت مد نفوذها إلى مناطق عمان للاعتبارات التى كانت تدفع بالدولة العباسية للسيطرة على سواحل عمان. وقد أولى البويهيون اهتماما خاصا بعمان وكانت غايتهم من ذلك تحقيق دافعين، الأول سياسي من أجل توسيع حدود دولتهم بعد أن سيطروا على بلاد فارس والعراق وكرمان، لذلك فكروا بضم سواحل الخليج العربي إلى ممتلكاتهم. أما الدافع الثاني فكان اقتصادي، فظهرت رغبة عند البويهيين في الحصول على نصيب وافر من تجارة سواحل الخليج العربي، فقد أتصف بعض الأمراء البويهيين بحب الثروة وجمع الأموال. فالسيطرة على عمان كانت في أكثر صورها شكلية وغير مستقرة، بسبب ما تتمتع به منطقة عمان من موقع جغرافي بعيد عن مركز الخلافة العباسية في بغداد من جانب، وطبيعة أرضها الصحراوية الجبلية التى تساعد أهالها على الاعتصام والمقاومة من جانب آخر، فضلا عن تباين سكانها من الزنج والخوارج.

الإباضية ومنهجهم في تفسير القرآن الكريم - الصائغ, ناصر بن محمد بن صالح (مجلة العلوم الشرعية, 2012)
فهذا بحث بعنوان: الإباضية ومنهجهم في تفسير القرآن الكريم " وجاء البحث للتعريف بمنهج من مناهج الفرق المبتدعة في التفسير التي ظهر تأثير مذهبها على تفاسيرها، وقد دفعني إلى اختياره أمور منها: 1ـ أن الإباضية فرقة معاصرة، لها جهودها ونشاطاتها في نشر مذهبها. 2ـ أن هذه الفرقة تسمي نفسها أهل الحق وأهل الاستقامة، وتستدل بالقرآن الكريم في التدليل على عقائدهم، مخالفة لمنهج السلف في التفسير، فوجب معرفة منهجهم في تفسير القرآن للحذر من أباطيلهم. وقد عرف البحث بفرقة الإباضية، وعقائدها، وعلاقتها بالخوارج، وأبان بعضاً من عقائد الإباضية، كما أبان فقه الإباضية ومواطن انتشارهم، وجاء فيه البيان عن منهج الإباضية في التفسير، وقد اشتمل بيان منهجهم في التفسير على ما يلي: أولاً : تأويل ما يخالف عقيدتهم من آيات القرآن. ثانياً: تأثرهم بالمعتزلة وموافقتهم لهم في كثير من الآراء والمعتقدات، ثالثاً: إشادتهم بمذهبهم الإباضي وذم ما سواه من المذاهب الأخرى. رابعاً: تفسير القرآن بالقرآن. خامساً تفسير القرآن بالسنة. سادساً: الإكثار من إيراد الإسرائيليات. سابعاً: الاهتمام بالمسائل النحوية والبلاغية. ثامناً الاهتمام بالقراءات والعناية بتوجيهها. تاسعاً: العناية بالأحكام الفقهية. عاشراً: الشدة على من خالفهم. ثم م ختم البحث بخاتمة اشتملت على أهم نتائج البحث ومنها: 1ـ التعريف بفرقة الإباضية وببعض عقائدهم وأماكن انتشارهم. 2 ـ تقرير أن الإباضية فرقة ضالة من فرق الخوارج، وبيان ارتباطهم بهم. 3ـ أظهر البحث تأثر الإباضية بالفكر الاعتزالي. 4ـ قلة النتاج التفسيري للخوارج بشكل عام. ومنهم فرقة الإباضية، وأبرز البحث أسباب ذلك. 5ـ بلغت تفاسير الإباضية التي وقفت عليها ـ تسعة تفاسير، المطبوع منها خمسة تفاسير. 6 ـ سلك الإباضيون كغيرهم من الفرق المبتدعة منهج التأويل لآيات القرآن فيما يخالف معتقدهم.
Keywords: Coran -- Commentaires

حول المسالك الرابطة بين جزيرة جربة واليابسة: طريق القنطرة وطريق الجمال من خلال معطيات المصادر - الحبيب, محمد علي (الكراسات التونسية, 2012)
اقتصرت المباحث التي خاضت في شبكة الطرقات بين جزيرة جربة والمجال القاري إما على دراسة طريق القنطرة الذي شيد منذ الفترة الرومانية أو المسلك البحري الذي يفصل أجيم على مضيق الجرف. نحاول في هذا المقال رفع الالتباس والخلط الذي سقطت فيه دراسات عديدة، عربية وغربية على السواء، بين الطريقين البريين "القنطرة" و"الجمال" اللذان ربطا جزيرة جربة بالمجال القاري من جهة بحيرة بوغرارة الجنوبية. أما المنهج المتبع فهو إعادة قراءة معطيات النصوص المصدرية الكلاسيكية (العربية والأجنبية) ومقارنة معلومات الإخباريين بتلك التي وصلتنا عن طريق الرحالة والبحارة المتوسطيين. هذه المعطيات كفيلة لوحدها بتبين وجود طريقين منفصلين لكل منهما تاريخه ووظيفته

Developing a Territory Balanced Scorecard approach to manage projects for local development: Two case studies - Ioppolo, Giuseppe; Saija, Giuseppe; Salomone, Roberta (Land Use Policy, 2012)
Keywords: Urbanisme -- Djerba

مؤتمر الفكر الإباضي الثالث جامعة نابولي ـ إيطاليا 28 - 30 مايو 2012 م - الحجري, محمد بن سعيد (التفاهم, 2012)

لمحة عن المساجد الأثرية في محافظة مسقط (سلطنة عُمان) - الجلاصي, مدیحة (التفاهم, 2012)
Keywords: Monuments -- Oman

من مآثر علم الكلام الإباضي بشمال إفريقيا: نظرة إجمالية - الشيخ, محمد (التفاهم, 2012)
Keywords: Philosophie islamique

النص والأرض وجدليات العلائق: علم الكلام الإباضي نموذجا - الإسماعيلي, أحمد (التفاهم, 2012)

Rôle de la migration dans la valorisation et la conservation des patrimoines socioculturels : cas de lřîle de Djerba - Gammoudi, Taoufik (Revue des Régions Arides, 2012)
Keywords: Démographie -- Djerba

Der Terror-Anschlag auf Djerba aus rechtlicher und rechtspolitischer Sicht - Schmid, R.; Tonner, K. (ReiseRechts aktuell, 2012)
Keywords: Attentats -- Djerba -- 2002

Les marges renaissantes : Amazigh, Juif, Noir. Ce que la révolution a changé dans ce « petit pays homogène par excellence » qu’est la Tunisie - Pouessel, Stéphanie (L’Année du Maghreb, 2012)
L’article envisage les revendications issues de certains groupes « minoritaires » comme une des lames de fond qui bouscule le « monolithisme culturel » officiel de la Tunisie post-dictatoriale. La focalisation sur certains citoyens qui s’affirment sur la scène culturelle et politique en tant que membres d’un groupe minoré (amazigh, noir, juif) permettra de comprendre comment ils tentent de mettre au centre du débat public la question de la pluralité ethnique et confessionnelle de la société tunisienne. L’inscription du répertoire de la « diversité culturelle » prend ainsi toute sa place dans les enjeux politiques qui suivirent le 14 janvier 2011 puis les premières élections démocratiques visant à constituer une assemblée constituante. Dans cette phase de refonte des représentations de la « nation » se développent des discours inédits sur la discrimination, la reconnaissance ou encore la mémoire plurielle : qu’en est-il de la place de l’héritage juif dans un pays où domine l’islam politique ? Pourquoi inscrire la lutte contre la discrimination raciale dans la nouvelle constitution ? Enfin, comment se constitue une amazighité tunisienne sous pression du militantisme amazigh panmaghrébin ?
Keywords: Berbérisme -- Tunisie

La communication touristique face à la menace terroriste : Le cas de la Tunisie après les attentats du 11 septembre 2001 et Djerba 2002 - Viallon, Philippe; Daldoul, Sarra (Revue des Régions Arides, 2012)
Keywords: Attentats -- Djerba -- 2002

L'activisme de Salah ben Youssef en faveur de la question tunisienne à la lumière d'une nouvelle lettre envoyée à l'une des personnalités italiennes en 1952 - Temimi, Abdeljelil (Revue d'Histoire Maghrébine, 2012)
Keywords: Ben Youssef, Salah 1907-1961

L’île de Djerba à travers le récit du voyageur Allemand Ewald - ʿAnnābī, Ḥasan al- (Mediterranean world, 2012)
Keywords: Récits de voyage -- Djerba

The Pact (amana) between Muawiya ibn Abi Sufyan and Amr ibn al-As (656 or 658 CE): 'Documents' and the Islamic Historical Tradition - Marsham, Andrew (Journal of Semitic Studies, 2012)
A written pact between Mu'āwiya ibn Abī Sufyān and ‘Amr ibn al-‘Āṣ is widely discussed in the early Arabic historical tradition. However, only Ibn Sa'd (d. 845) preserves a copy of it. Analysis of the form, content and context of this ‘document’ shows it to have much in common with other early agreements, such as the so-called ‘Constitution of Medina’ and the ‘Ṣiffīn Arbitration Agreement’. It also suggests that it reached Ibn Sa'd from al-Wāqidī (d. 823). The ‘document’ has some unusual features — notably a date that suggests a different context to that given by both Ibn Sa'd and modern commentators. On balance, however, it seems that the ‘document’ may indeed reflect elements of an original agreement. Nonetheless, no single ‘document’ from this early period should be relied upon in isolation; rather such texts should be viewed as a corpus in which evolutions in form and content can be identified.

Iṣlâḥ ibâḍite et intégration nationale : vers une communauté mozabite ? (1925-1964) - Jomier, Augustin (Revue des mondes musulmans et de la Méditerranée, 2012)
Constitué en mouvement social au cours des années 1930, principalement sous la direction du cheikh Bayyûḍ, l’iṣlâḥ constitue un élément majeur de l’histoire et de la mémoire du Mzab à l’époque contemporaine. Si les oulémas réformistes ont principalement affirmé leur action dans le domaine éducatif, ils se sont aussi engagés dans une action politique, à la fois à l’échelle locale, par la conquête des institutions « traditionnelles » du Mzab et, à l’échelle algérienne, en entrant ouvertement dans le jeu institutionnel colonial à partir de 1947. Cette dynamique religieuse et les actions politiques qu’elle a générées se sont accompagnées d’une réflexion sur le rapport de l’ibadisme aux autres madhâhib et sur la place des berbères dans l’histoire du Maghreb arabe et de l’Algérie. Ainsi par leur action politique, les oulémas réformistes se sont affirmés comme les leaders d’une communauté qu’ils construisaient, en réinterprétant les institutions traditionnelles. Au même moment, par leur réflexion dans le domaine de l’historiographie, ils ont œuvré à articuler les identités ibâḍite et mozabite à celle, en construction, de la nation algérienne. Dans cet article, je me propose d’interroger le rôle que les oulémas réformistes ont joué dans ce processus double, politique et intellectuel, de construction de la population ibâḍite et mozabite en communauté politique, processus qui a accompagné son entrée dans l’ensemble algérien. Pour cela je m’appuierai sur certains textes des oulémas de l’iṣlâḥ et de l’historiographie du mouvement, ainsi que sur les archives coloniales (ANOM, Aix-en-Provence) et celles des Missionnaires d’Afrique (Pères Blancs, Rome).
Keywords: Réformisme -- Mzab

Peuplement et organisation du territoire dans une région d'implantation ibâḍite : le Jebel Demmer dans le sud-est de l'Ifrîqiya (ve/xie- ixe/xve siècle) - Hassen, Mohamed (Revue des mondes musulmans et de la Méditerranée, 2012)
Cet article s’intéresse aux formes de peuplement et d’organisation du territoire dans le Jebel Demmer à l’époque médiévale, lorsque cette région du sud de l’Ifrîqiya comportait encore une importante population ibadite, elle-même scindée en plusieurs groupes. Après avoir évoqué la délimitation du territoire à l’époque médiévale, l’article propose une réflexion sur l’apparition et la typologie des qsûr. Leur développement en tant qu’unités fondamentales dans l’organisation de l’espace local est rattaché aux invasions hilaliennes, qui provoquèrent un afflux important de populations ibâḍites dans cette région, qui devint pour quelque temps l’un des bastions de cette minorité en Ifrîqiyya. Enfin, la diffusion du malékisme est évoquée, faisant ressortir la lenteur de ce processus, encore inachevé au début du xve siècle.

Sedrata : l’élaboration d’un lieu de mémoire - Aillet, Cyrille; Gilotte, Sophie (Revue des mondes musulmans et de la Méditerranée, 2012)
Les vestiges ensablés de Sedrata, à une dizaine de kilomètres au sud de la ville actuelle de Ouargla, font aujourd’hui figure de lieu de mémoire pour l’ibadisme maghrébin. Chaque année un pèlerinage s’y déroule, attirant des représentants des communautés ibadites du Maghreb mais aussi des visiteurs de plus en plus nombreux. Plus qu’à une description du site archéologique, fouillé par l’archéologue suisse Marguerite van Berchem entre 1950 et 1955, cet article s’attachera à décrypter son importance dans la mémoire et dans l’imaginaire historiques de l’Algérie, de la période coloniale à nos jours. Nous nous attachons tout d’abord à la découverte du lieu, décryptée à la lumière des grands voyages d’exploration du Sahara de la fin du xixe siècle. La récupération académique du lieu, à l’orée du xxe siècle, est l’occasion de réfléchir sur les grilles d’interprétations ethnicisantes et culturalistes mises en place pour l’identification et la compréhension des vestiges et des décors de stuc. Nous nous arrêtons sur les travaux de M. van Berchem, qui firent de Sedrata un élément du « patrimoine » national algérien. Nous suivons également les derniers développements du mythe de Sedrata dans les écrits du Père Blanc J. Lethielleux, qui entremêlent de façon indéchiffrable traditions historiques et traditions locales. Enfin, nous nous intéressons à l’action des associations locales pour la sauvegarde du site et pour le rayonnement du pèlerinage.
Keywords: Archéologie -- Sedrata

North African and Omani Ibâḍî Accounts of the Munâẓâra: A Preliminary Comparison - Gaiser, Adam R. (Revue des mondes musulmans et de la Méditerranée, 2012)
This chapter compares Western/North African and Eastern/Omani Ibâḍî accounts of the munâẓara (debate) that took place at Ḥarûrâ’ before the Battle of Nahrawân to reveal two similar yet distinct traditions. A further comparison with non-Ibâḍî (i.e. al-Ṭabarî, al-Balâdhurî, al-Baghdâdî, etc.) versions of the debate shows that it is the Western/North African tradition that shares certain features and narrative structures with non-Ibâḍî accounts. The key to understanding these particular textual configurations is the figure of the last Basran Imâm, Abû Sufyân Maḥbûb Ibn al-Raḥîl. Abû Sufyân wrote his Kitâb Abî Sufyân on the commission of the Rustumid Imâm Aflaḥ Ibn ‘Abd al-Wahhâb, and likely incorporated Basran and Kûfan Ibâḍî traditions that did not gain wide currency among Ibâḍîs in Oman. For this reason, non-Ibâḍî and Western munâẓara accounts share certain characteristics that are not present in Eastern accounts, even though Oman is geographically closer to the places where non-Ibâḍî accounts likely originated.

The authenticity of the letter of ‘Abd Allâh b. Ibâḍ to ‘Abd al-Malik - Madelung, Wilferd (Revue des mondes musulmans et de la Méditerranée, 2012)
The so-called first letter of Ibn Ibâḍ was long considered in modern scholarship as an authentic letter of ‘Abd Allâh b. Ibâḍ, the reputed founder of the Ibâḍiyya sect, to the Umayyad caliph ‘Abd al-Malik. This was questioned first by John Wilkinson and then by Michael Cook in his book on Early Muslim Theology, who proposed that the letter was written rather by Jâbir b. Zayd to the Muhallabid amîr ‘Abd al-Malik b. al-Muhallab. In his recent book on Ibadism, John Wilkinson has argued that the letter was addressed to ‘Abd al-Malik, the son of the caliph ‘Umar II, and that Jâbir b. Zayd could not have been its author. It will be argued in this paper that the letter is an authentic letter of ‘Abd Allâh b. Ibâḍ addressed to the son of ‘Umar II. Ibn Ibâḍ was not the founder of the Ibâḍiyya sect, but rather a contemporary and rival of Abû ‘Ubayda Muslim b. Abî Karîma.

AL-SALIMI, A., and W. MADELUNG (eds.) — Early Ibadi Literature. Abu l-Mundhir Bashir b. Muhammad b. Mahbub, Kitab al-Rasf fi l-Tawhid, Kitab al-Muharaba and Sira - Custers, Martin H. (Bibliotheca Orientalis, 2012)
Keywords: Recension

Trends in Religious Reform on the Arabian Peninsula - Salimi, Abdulrahman al- (Hemispheres, 2012)
This article comparatively assesses the relationship of Arabian Peninsula governments to modern Islamic reform movements after the formation of nation-states by the British Government in post-Ottoman Arabia. Over the last half century the region of the Arabian Peninsula has experienced an Islamic awakening that has played an integral role in the process of modernization in Arabian states. There are three aims of this study: 1) to examine the influence of the traditional Islamic schools of theology on re-shaping the identities of Arabian states. 2) to explore the degree to which the governments of the nation states and the prior political establishments informed the contemporary vision of religious reform 3) to consider the impact that the recent wealth of Arabian States, especially the wealth of the GCC countries, has had on the creation of the modern Islamic revival since the discovery of oil. [PUBLICATION ABSTRACT]

Adam Gaiser, Muslims, Scholars, Soldiers. The Origin and Elaboration of the Ibadi Imamate Traditions, New York: Oxford University Press, 2010. 203 S., ISBN 0-19-973893-9, 978-0-19-973893-9 - Aillet, Cyrille (Der Islam, 2012)
Keywords: Recension

De nouvelles données sur les origines de l’ibadisme et l’élaboration de la théorie de l’imamat - Prevost, Virginie (Arabica, 2012)

Mağmāğ et les sept savants : la création du Dīwān al-ʿazzāba - Prevost, Virginie (Acta Orientalia, 2012)
Keywords: Fiqh -- Traité -- 11e siècle

A forgotten collection: the Libyan ethnobotanical exhibits (1912-14) by A. Trotter at the Museum O. Comes at the University Federico II in Naples, Italy - De Natale, Antonino; Pollio, Antonino (Journal of Ethnobiology and Ethnomedicine, 2012)
Keywords: Botanique -- Djebel Nefousa

Local hosting and transnational identity - Hoffman, Katherine E. (Forced Migration Review, 2012)
Initially, as groups of migrant workers crossed into Tunisia en route to the airport on the Tunisian island of Djerba, Tunisian villagers organised cooking crews, with men cooking together in community centres and women cooking separately in their homes. The shared language and similar customs facilitated Libyan integration into Tunisian villages and small towns. Since pre-schoolaged Libyan children in the Nafusa Mountains usually only speak Tamazight, Libyan women felt reassured living among Tamazight speakers.

أقوال قتادة : مخطوط إباضي ثمين من جزيرة جربة - Ess, Josef van (دراسات, 2012)

The Manufacture of Raw Brick from the Saharan Sand-Based Mortar of Ouargla (Located in the Septentrional Sahara, Algeria) for use in Arid Regions - Leghrieb, Youcef; Mitiche, Ratiba; Bentebba, Mohammed Taher; Djouhri, Mohammed; Kriker, Abdelouahed (Arabian Journal for Science and Engineering, 2012)
Keywords: Artisanat -- Ouargla

John C. Wilkinson, Ibâḍism: Origins and Early Development in Oman, Oxford Oriental Monographs (Oxford, U.K.: Oxford University Press, 2010). Pp. 500. $185.00 cloth. - Madelung, Wilferd (International Journal of Middle East Studies, 2012)
Keywords: Recension

La politique coloniale à l'égard des juifs : l'expulsion des Kabla, banquier de Djerba, au milieu des années trente - Sahbani, Karima (Revue d'Histoire Maghrébine, 2012)
Keywords: Judaïsme -- Djerba

African Identities, Afro-Omani Music, and the Official Constructions of a Musical Past - Harthy, Majid H. al- (The World of Music, 2012)
Based on dissertation research in the port city of Sur, historically significant both for trans-oceanic seafaring and trade, and more specifically for its connection to the east coast of Africa, this article analyzes the African-derived performance genres that dominate Sur's music scene within an ever-elusive concept of Africa. The sacred healing rituals zār, mikwarā, and ṭambūra; and the secular genres, mdema, and fann is-ṣawt have been renamed funūn taqlīdīya or traditional arts, national nomenclature that collects the myriad traditions of the country while marginalizing differential identities. Rhetorically, Suri musicians not only adopt, they also emphasize their national Omani identity, while expressing their African identity as of the "other." Musically, however, their approach to performance, including the use of Swahili texts, the predominance of body movement, and multi-layered musical textures produced by a variety of instruments from East Africa, reveals, I argue, the musicians' African identity as a "self." The seemingly binary "self" identities articulated by Suri musicians through two differing modes of expression (rhetoric and performance) illustrate not only the problematic nature of the concept of Africa in Oman, but also highlights how simplistically the African presence in Oman has been treated in the music scholarship of this country.
Keywords: Musique -- Oman

The Musical Design of National Space and Time in Oman - Rasmussen, Anne K. (The World of Music, 2012)
This article unpacks ethnographic research conducted in 2010–2011 and in 2012 among cultural activists and reformers who are using music as a generative force toward the development of collective identities in a geopolitical space. I analyze three domains of cultural production and consider how the Sultan's initiatives have resulted in the embodiment of artistic consumption and connoisseurship that are required for musical life in the public sphere: first are the Sultan's privately controlled military bands, Arab music ensembles, and symphony orchestra; second are public arts festivals that nurture and celebrate traditional music and dance; third is the domain of Omani popular music facilitated by Arab regional interculturalism and media flows that depend significantly on practitioners from Egypt, Iraq, and other Gulf states. I show how these domains of music and dance work to enable the imagination of a cultural space and time for Oman and its historical and contemporary relationships with the Arab world, Africa, Asia, and "the West." The ethnographic focus on the Salalah Festival in the Dhofar province, provides a close-up shot of the workings of the state at the local level in a context that is both far from the control of the capitol city, Muscat, but that also reproduces many of the relations of dominance and resistance that is an inevitable artifact of political power and cultural policy.
Keywords: Musique -- Oman

On the Decks of Dhows: Musical Traditions of Oman and the Indian Ocean World - Ulaby, Laith (The World of Music, 2012)
This article situates the musical traditions of Oman in the broader context of the Arabian Peninsula and Indian Ocean. Trade, slavery, and pilgrimage prompted the creation of networks that extended across the Indian Ocean for hundreds of years and facilitated deep and lasting cultural exchanges. Oman has played an important role in these networks and this is deeply reflected in many of the local musical traditions. Since about the middle of the 20th century, countries in the Arabian Gulf (sometimes referred to as the GCC, Gulf Cooperation Council, plus Yemen) have made strides toward establishing independent nationalism in the contemporary race for unique identities; however, their histories, peoples, and musical traditions, particularly those of nomadic Bedouins and coastal seafaring populations, have overlapped for many centuries. I attempt to sketch out some comparisons, particularly in terms of performance practice, between Oman and the rest of the Gulf States with a focus on maritime music, the music that occurred "on the decks of dhows," the traditional sailing vessel of the Arabian Gulf. My theoretical grounding for this article engages with frameworks for cultural transmission and explores their relevance to the Gulf. By looking at historical accounts and previous scholarship, alongside ethnographic research, I describe some of the conduits for sharing musical influence with the broader Indian Ocean cultural space. Lastly, I critically examine some of the historiographies that have been created around these exchanges and their valence to the political economy of cultural heritage in the region.
Keywords: Musique -- Oman

Music in Oman: an Overture - Harthy, Majid H. al-; Rasmussen, Anne K. (The World of Music, 2012)
Keywords: Musique -- Oman

« Et il les envoya prêcher le royaume de Dieu et guérir les malades... » (Luc, IX, 2). Soigner les populations au Sahara : l'hôpital mixte de ghardaïa (1895-1910) - Fredj, Claire (Histoire et missions chrétiennes, 2012)
Keywords: Missionnaires -- Algérie

Ibâḍî Reformism in Twentieth-Century Algeria : The Tafsîr of Shaykh Ibrâhîm Bayyûḍ - Hoffman, Valerie J.; Shueili, Sulaiman bin Ali bin Amir al- (Revue des mondes musulmans et de la Méditerranée, 2012)
Shaykh Ibrâhîm b. ‘Umar Bayyûḍ of Wâdî Mzâb (1899-1981), leader of Ibâḍî reformism in Algeria after the death of Muḥammad b. Yûsuf Aṭfiyyash (1820-1914), delivered a public commentary on the Qur’an from 1935-1980, which was recorded beginning with Sûra 17:70. Shaykh Bayyûḍ claimed to follow the goals and methodology of Muḥammad ‘Abduh and Rashîd Riḍâ’s Tafsîr al-Manâr. This article analyzes Shaykh Bayyûḍ’s commentary in comparison to, on the one hand, Aṭfiyyash’s two Qur’an commentaries (Hamayân al-zâd ilâ dâr al-ma‘âd and Taysîr al-tafsîr), in order to determine its relationship to earlier modern Ibâḍî reformism, and, on the other hand, to Tafsîr al-Manâr, in order to determine its relationship to that strand of Sunni reformism. It finds that Bayyûḍ’s commentary, like Tafsîr al-Manâr, promotes Islamic unity and eschews theological dogmatism, while attacking customs deemed antithetical to Islamic teaching and making sometimes lengthy digressions on topics of contemporary social and political importance. Nonetheless, Bayyûḍ remains faithful to Ibâḍî doctrine on topics on which Ibâḍîs and Sunnis differ, and there is little evidence that he argued for Islam’s compatibility with liberal values ; on the contrary, at several points in his commentary he states that modern ideas and customs constitute a real threat to Islam.
Keywords: Bayyūḍ, Ibrāhīm ibn ʿUmar (1899-1981); Coran -- Commentaires -- 20e siècle

The Mzab foggara: an original technique for collecting the water rising - Remini, Boualem; Achour, Bachir; Ouled Belkhir, Cheikh; Baba Amar, Dahmane (Journal of Water and Land Development, 2012)
Abstract This paper describes for the first time an original foggara, different from the classical foggara (foggara of Gourara) which collects water from the Intercalary Continental aquifer. Located in the middle of the Mzab River, this hydraulic system called the Mzab foggara is intended to exploit the flood waters. Two missions were carried in 2009 and 2010 in the Mzab Valley to describe the hydraulic system. The Mzab foggara constitutes of a gallery of ovoid form 200 m long equipped with 9 air shafts and a 900 m long seguia. The foggara of the Mzab River can drain water flow of 5 m3·s-1 to irrigate western part of the palm plantation of Ghardaia (located 600 km south of Algiers).

Contribution à l’étude d’un mot voyageur : Chleuh - Agrour, Rachid (Cahiers d'études africaines, 2012)
Keywords: Linguistique

L'église orthodoxe en Tunisie - Chaillot, Christine (Le messager orthodoxe, 2012)
Keywords: Christianisme -- Djerba

Etat environnemental de la lagune de Boughrara et ses alentours deux ans après les travaux d'aménagement et d'élargissement du pont d'el Kantara - Guetat, Fatma; Sellem, Feriel; Akrout, F; Brahim, Mouldi; Abdelfattah, Atoui; Romdhane, S.; Daly, Et (2012)
L'étude de l'état environnemental de la lagune de Boughrara a été réalisée deux ans après la mise en service du nouveau pont El Kantara. Les paramètres étudiés dans l'eau (nitrites, nitrates, ammonium, azote, phosphore total, chlorophylle a) et le sédiment (matière organique, faciès sédimentaire) ont été analysés dans trois zones de la lagune appartenants à divers contextes géographiques et environnementaux. Les résultats obtenus ont montré d'évidents signes d'amélioration des conditions générales de cet écosystème. Les distributions spatiotemporelles et saisonnières des paramètres étudiés indiquent que les teneurs trouvées atteignent le seuil d'eutrophisation pas mal de fois mais restent toujours inférieurs à ceux mentionnés par la DGPA en 2000 avant les travaux d'aménagement. L'analyse granulométrique des sédiments superficiels reflète un fond à sables moyens à fins à des proportions différentes en matière organique selon les zones. ABSTRACT Environmental state of the Boughrara lagoon and his surroundings two years after alteration work and of extension of the bridge of el kantara : The present study aims to characterize water quality and sediment in Boughrara lagoon and its surrounding two years after the construction of new bridge. Abiotic parameters (water and sediment) are calculated in three areas with different geographical and environmental contexts. The results have shown clear signs of improvement in terms of the ecosystem. The spatiotemporal distributions of physicochemical parameters of water indicate that the levels found below the threshold of eutrophication quite a few times but are still lower than those reported by DGPA (2000). The size analysis of surface sediments shows that the bottom of the three underwater zones explored is covered mainly by medium to fine sand rich in organic matter.

Automatic Measurement of Shoreline Change on Djerba Island of Tunisia - Bouchahma, Majed; Yan, Wanglin (Computer and Information Science, 2012)
Keywords: Littoraux -- Djerba

Spatial distribution and abundance of the megabenthic fauna community in Gabes gulf (Tunisia, eastern Mediterranean Sea) - El Lakhrach, H.; Hattour, A.; Jarboui, Othman; Elhasni, K.; Ramos-Espla, A.A. (Mediterranean Marine Science, 2012)
Keywords: Biologie -- Djerba

Physico-Chemical Characterization and Analysis of Various Tunisian Olive Oil Varieties: Minor Compounds and Fatty Acids - Slim, Smaoui; Hajer, A; Ben-Hlima, Hajer; Jarraya, Raoudha; Kamoun, Nozha; And, Raoudha; Mohamed, Damak (Journal- Chemical Society of Pakistan, 2012)
Given the growing interest of consumers worldwide in safe, healthy and good quality olive oil, the present study aimed to investigate a number of Tunisian virgin olive oil varieties in an attempt to procure physico-chemical characteristics of interest to the local and global olive oil industry, particularly in terms of variety and area of cultivation. Eight samples collected from Chetoui, Chemlali, Zarrazi, and Zalmati Tunisian cultivars located at Sfax, Thibar, Zarzis, and Jerba were employed. Various physic-chemical parameters were investigated, including free acidity, peroxide value, UV absorption, pigment concentrations, oxidative stability, fatty acid composition, phenolic compounds and sterols. The findings revealed high heterogeneity within and between the varieties. The Chemlali Jerba" and Zarrazi oil samples showed high oleic acid and low linoleic acid concentrations, rich phenolic compounds, and high stability. The sterols fractions in Chemlali Sfax, Chemlali Jerba, and Zalmati olive oils displayed high levels of β-sitosterol, campesterol, and ∆-5-avenasterol. Overall, the olive oil from Chemlali Jerba presented higher levels of natural antioxidants and oxidative stability. Its chemical composition was also noted to be particularly interesting in terms of fatty acid contents, minor components, and antioxidants, namely sterols, tocopherols, carotenoids, and phenolic acids.
Keywords: Botanique -- Djerba

Comparing Ibâḍî and Sunnî law in Baṣra : the case of the zakât on cattle - Francesca, Ersilia (Revue des mondes musulmans et de la Méditerranée, 2012)
Keywords: Fiqh

Entre le massif de l’Aurès et les oasis : apparition, évolution et disparition des communautés ibâḍites du Zâb (viiie-xive siècle) - Amara, Allaoua (Revue des mondes musulmans et de la Méditerranée, 2012)

Les enjeux de la bataille de Mânû (283/896) - Prevost, Virginie (Revue des mondes musulmans et de la Méditerranée, 2012)
Keywords: Conflits -- Afrique du Nord

L’ibâḍisme, une minorité au cœur de l’islam - Aillet, Cyrille (Revue des mondes musulmans et de la Méditerranée, 2012)
Keywords: Ibadisme -- thèmes et motifs

Les Ibadites et leurs écrits (VIIIe-Xe siècles) - Benchikh-Boulanouar, Saïda (Outre-Mers. Revue d'histoire, 2012)
Keywords: Bibliographie -- Mzab